Durable and changing views of English: a diachronic thematic analysis of National Day Rally speeches in Singapore. Issue 3 (2nd September 2019) - Wong, Angelia; Tupas, Ruanni
Abstract: Diachronic studies which rely chiefly on official pronouncements on languages or language policies are rare. Focusing on Singapore, a review of scholarly work on language ideologies and National Day Rally (NDR) speeches reveal that researchers have yet to conduct a diachronic analysis of the speeches delivered from 1966 to 2016. This study therefore conducts a diachronic thematic analysis of the speeches delivered since independence to find out whether Singaporean politicians' views of English have changed over time. We found that views such as the state's conception of English as a unifying language and the adoption of a pragmatic view towards English have been consistent over the years. Moreover, views of English (varieties of English) that have morphed over the years or are short-lived could be due to conflicting perceptions which depict the government to be incongruous in their views or the state as capitulating to the demands of everyday Singaporeans.